On analysis of double-impact test of 1500-kg vehicle into w-beam guardrail system - Krzysztof Wilde; Dawid Bruski; Stanisław Burzyński; Jacek Chróścielewski; Łukasz Pachocki; Wojciech Witkowski (Archives of Civil Engineering, 2021)
Every day on roads many scenarios of accidents may occur. One of the measures to minimize their consequences is road safety barriers. Finite Element analyses are being increasingly used to support the physical testing of these devices. The paper addresses the issue of a secondary impact into the previously damaged w-beam guardrail system. This situation belongs to one of the most dangerous which can happen on roads and may cause serious hazards, especially if the vehicle goes through the barrier. To evaluate the crashworthiness of the road barrier, the computational model of the crash test was developed and validated against the full-scale crash test. Then two simulations of TB32 crash tests were conducted on both damaged and undamaged road barriers to assess the influence of damage on the effectiveness of the safety system during vehicular impact. The study has revealed that the partially damaged system preserved some of its original functionality.